Penerapan dan Pendampingan Pembuatan QR Code sebagai Sarana Efisiensi Pemasaran Kambing di Pertanian Terpadu Kelubir (PTK) Kecamatan Tanjung Palas Utara Kabupaten Bulungan Kalimantan Utara - Abdussalaam, Falaah; Rosmayati, Siti; Handari Adji, Widwi; Paryanti, Dini; Trimawan, Anang; Fery Maulana, Syaifudin; Deo Ginoki, Algin; Wahyudi (LPPM Politeknik Piksi Ganesha, 2024)
Efficient marketing is the main key to increasing livestock farmers' income and strengthening local food security. In an effort to increase the efficiency of goat marketing in the Kelubir Integrated Agriculture (PTK) area located in Kelubir Village, North Tanjung Palas District, Bulungan Regency, North Kalimantan Province, the Piksi Ganesha Polytechnic collaborates with PT Pesona Khatulistiwa Nusantara (PKN) and synergizes with the Regency Government Bulungan to carry out community service activities that focus on implementing and assisting in making QR codes as an innovative solution that can accommodate information on the development of goat livestock, starting from the age of the animal, body weight, pedigree, and the health status of the goat. This service activity uses a participatory approach that involves farmers directly with a question-and-answer session method and technical assistance related to the use of QR Code technology. The results of this service provide benefits that are felt by both breeders and consumers/potential buyers because it provides convenience and transparency regarding data on goat livestock to be purchased. From the results of the service satisfaction survey in the form of QR Code implementation and assistance carried out to 8 respondents, there were 62.5% of respondents said they were very satisfied and 37.5% said they were satisfied